Modeling of a superheater for a combined cycle power plant - Mohamad Idris, Faridah; Yusof, Rubiyah; Khalid, Marzuki (2000)

(untitled)
In this paper, we derive the time-dependent equations of a superheater of a combine cycle power plant. Simulations of the superheater are done on Matlab Simulink. We show the results of modeling the superheater based on several variations of its outputs